Correlation of Body Mass Index and Waist-Hip Ratio with Severity and Complications of Hyperlipidemic Acute Pancreatitis in Chinese Patients - Lixin Yang; Jing Liu; Yun Xing; Lichuan Du; Jing Chen; Xin Liu; Jianyu Hao (Gastroenterology Research and Practice)
Hyperlipidemic acute pancreatitis (HLAP) is characterized by critical condition and high recurrence rate compared with non-HLAP. We conducted this study to investigate the value of body mass index and waist-hip ratio in predicting severity and local complications in HLAP. 96 patients with HLAP were categorized by body mass index and waist-hip ratio, respectively. According to the body mass index, they were divided into 3 groups, including normal weight, overweight, and obesity. According to the waist-hip ratio, they were divided into central obesity group and no central obesity group. The body mass index and waist-hip ratio were compared in severity, local complications, and systematic complications of HLAP, using chi-square test and Monte Carlo simulations. The body mass index and waist-hip ratio were correlated with the severity of acute pancreatitis (MAP, MSAP, and SAP), respiratory failure, and circulatory failure in HLAP (p<0.05), but not correlated with the local complications (walled-off necrosis, pancreatic abscess, and pancreatic pseudocyst), renal failure, and gastrointestinal bleeding.The body mass index and waist-hip ratio are valuable in predicting severity and complication in HLAP. We demonstrated that obese patients had an increased risk of developing more serious condition and more complications in HLAP.